The influence of the Pilates method on quality of life and bone remodelling in older women: a controlled study - Gandolfi, Nathalia Regina Sabatini [UNESP]; Corrente, Jose Eduardo [UNESP]; De Vitta, Alberto; Gollino, Loraine [UNESP]; Mazeto, Gláucia Maria Ferreira da Silva [UNESP] (Springer Nature, 2020)
Purpose: The objective of this study was to evaluate the effects of the Pilates method on quality of life and bone remodeling markers in a group of older women. Methods: A longitudinal prospective study with intervention was performed on 40 women aged over 60 years; they were divided into two groups: one submitted to a 50-min Pilates exercise session once a week for 20 weeks (Pilates), and the other was not (Control). Both groups were compared for quality of life using the Medical Outcomes Study 36, and for bone-specific alkaline phosphatase (BSAP) and Type 1 collagen C-telopeptide (CTx) bone remodeling markers. Results: The Pilates group presented improvement in the quality of life evaluation scores: physical functioning (67.50 ± 18.88 × 86.25 ± 9.58; p = 0.0232), and physical component summary (65.00 ± 14.39 × 79.70 ± 3.83; p = 0.0220). The Pilates group also presented higher scores than that of Controls after the exercise program: physical functioning (86.25 ± 9.58 × 55.50 ± 20.83, p = 0.0003), physical role (100.00 ± 0.00 × 41.25 ± 46.79, p = 0.0009), emotional role (100.00 ± 0.00 × 48.33 ± 50.12, p = 0.0046), vitality (82.50 ± 14.28 × 60.25 ± 21.43, p = 0.011), physical component summary (79.70 ± 3.83 × 54.90 ± 15.05, p < 0.0001), and emotional component summary (74.10 ± 8.37 × 54.18 ± 22.55, p = 0.0111). No changes were noted in bone remodeling markers [CTx (0.39 ± 0.26 × 0.38 ± 0.22 ng/mL) and BSAP (10.73 ± 2.40 × 11.01 ± 3.56 μg/L)] and did not differ from the Control group both before (CTx: 0.39 ± 0.26 × 0.37 ± 0.17 ng/mL; BSAP: 10.73 ± 2.40 × 10.58 ± 3.49 μg/L; p > 0.05) and after exercise (CTx: 0.38 ± 0.22 × 0.38 ± 0.22 ng/mL; BSAP: 11.01 ± 3.56 × 9.85 ± 3.12 μg/L; p > 0.05). Conclusion: The group of women submitted to Pilates presented improved quality of life but without changes in bone remodeling.
Keywords: Aging; Bone remodeling; Exercise movement techniques; Exercise therapy; Quality of life